The Effect of Compressive Strength of Concrete with Styrofoam Waste Cement Coating on Acid Solution and Water Permeability: Pengaruh Kuat Tekan Beton Dengan Coating Cement Limbah Styrofoam Terhadap Larutan Asam Dan Permeabilitas Air - Sarjano, Belany Try Aji; Aswadi, Lalu Samsul; Yuwana, Dwi Sat Agus (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
This research analyze the effect of styrofoam cement coating as a protective layer on normal concrete in terms of physical quality and compressive strength when exposed to Natrium Sulfat acidic solution. Styrofoam-based cement coating is chosen due to water-resistant physical properties and its ability to reduce difficult-to-decompose waste. The method related to the effect of cement styrofoam coating as a liner with cylindrical concrete test objects measuring 15 cm in diameter and 30 cm in height and a quality of fc' 20 MPa, where its implementation is based on SNI 7656-2012. The cement coating used utilizes various mixture ratios of 0%, 40%, 50%, and 60% of the solvent weight in the form of Pertalite. The process of immersion in sodium sulfate acid solution, compressive strength testing, and permeability testing were conducted in the Laboratory, Universitas Tidar. The results indicate that the addition of styrofoam cement coating can reduce the corrosive impact of Natrium Sulfat acidic solution. The 60% styrofoam mixture variation showed the best results in three testing aspects: a post-curing compressive strength test value of 21.3621 MPa, a post-immersion in Natrium Sulfat acidic solution compressive strength test value of 20.7680 MPa, and a permeability test value of 7.03x10-9.